Análise dos atendimentos do SAMU 192: Componente móvel da rede de atenção às urgências e emergências - Almeida, Priscila Masquetto Vieira De; Dell'acqua, Magda Cristina Queiroz; Cyrino, Claudia Maria Silva; Juliani, Carmen Maria Casquel Monti; Palhares, Valéria De Castilho; Pavelqueires, Shirlene (Universidade Federal do Rio de Janeiro, 2016)
ABSTRACTObjective: To analyze the services provided by SAMU 192: the mobile component of the Urgency and Emergency Care Network, in the city of Botucatu, SP, Brazil.Methods: An exploratory-descriptive field study of a time series with a quantitative approach was performed. This study focused on the analysis of care provided by SAMU 192, between August 2011 and January 2012, based on 2635 service files.Results: There was a predominance of clinical occurrences and seizure as the main complaint (12.16%). The majority of victims (96.08%) were conscious upon arrival of the SAMU 192 team. The city's central region was the one that showed the greatest demand for care (25.83%). The main outcome of occurrences was the referral of victims to a hospital (81.61%).Conclusion: The present study showed the importance of SAMU 192 in the Urgency and Emergency Care Network. A high number of occurrences and the associations between several complaints and age, sex and place of occurrence stood out in this study.

RESUMENObjetivo: Analizar los atendimientos realizados por el SAMU 192 de Botucatu (SP).Métodos: Investigación de campo de serie histórica. Estudio exploratorio-descriptivo de enfoque cuantitativo, basado en el análisis de los registros de los servicios prestados por el SAMU 192, entre Agosto de 2011 y Enero de 2012, a partir de 2635 formularios.Resultados: Predominancia de eventos clínicos, siendo la crisis convulsiva la queja principal (12,16%). La mayor parte de las víctimas (96,08%) estaba consciente en el momento del servicio. La región central de la ciudad ha demostrado la mayor demanda por el servicio (25,83%). El principal resultado de las consultas fue la remisión de las víctimas al hospital (81,61%).Conclusión: Se comprueba la importancia del SAMU 192 en la Red de Atención de Urgencias y Emergencias, destacando el elevado número de llamadas, las asociaciones de quejas con la edad, el sexo y la región referente al atendimiento.

RESUMOObjetivo: Analisar os atendimentos realizados pelo SAMU 192: componente móvel da Rede de Atenção às Urgências e Emergências no Município de Botucatu/SP.Métodos: Trata-se de um estudo de campo, de série histórica, exploratório-descritivo de abordagem quantitativa, focado na análise das fichas dos atendimentos realizados pelo SAMU 192, entre agosto de 2011 e janeiro de 2012, totalizando 2635 fichas.Resultados: Houve predominância de ocorrências clínicas, sendo crise convulsiva a principal queixa (12,16%). A maioria das vítimas (96,08%) estava consciente no momento do atendimento. A região central da cidade foi a que apresentou maior demanda de atendimentos (25,83%). O principal desfecho dos atendimentos foi o encaminhamento das vítimas ao hospital (81,61%).Conclusão: O estudo mostrou a importância do SAMU 192 na Rede de Atenção às Urgências e Emergências, ressaltando o elevado número de atendimentos, as associações de várias queixas com idade, sexo e região do município referente ao atendimento.
Analysis of services provided by SAMU 192: Mobile component of the urgency and emergency care network
Análisis de las llamadas del SAMU 192: Componentes móvil de la red de atención a las urgencias y emergencias
Keywords: Nursing; Emergency Medical Services; Emergency; Enfermagem; Serviços Médicos de Emergência; Emergência